The Influence of Access to Green Jobs and Regulatory Incentives in Encouraging Sustainable Agricultural Practices on Young Entrepreneurs in the Agribusiness Sector : JEL Classification: Q01, Q18, Q56, J43, K32. - Ridwan Ridwan; Hasriani Hasriani; Syamsul Alam (Journal La Bisecoman, 2026)
This study examines the low adoption of sustainable agricultural practices among young agripreneurs, influenced by limited access to green jobs and weak regulatory incentives. The objective of the study is to analyze the influence of these two factors and identify the role of policy in strengthening the green economy ecosystem. The method used is a Systematic Literature Review (SLR), with data sources from reputable journals and relevant scientific literature. The data were analyzed using content analysis techniques to identify patterns of relationships between variables. The results indicate that access to green jobs and the effectiveness of regulatory incentives play a significant role in encouraging sustainable agricultural practices. In conclusion, the integration of green job opportunities and adaptive policies is key to accelerating the transformation of the agribusiness sector towards sustainability.